Análise da subsuperfície com Sondagem Elétrica Vertical (SEV) nas cidades de Capanema e Primavera, nordeste do estado do Pará - SILVA, Danilo da (2018)
Geological and geophysical studies based on the Vertical Electrical Sounding (VES) research technique were used in the identification of tectonic lithofacies of the carbonates and siliciclastic Neogene deposits, corresponding to the Pirabas and Barreiras Formations, and Quaternary sediments of the Post-Barreiras unit, which constitute the Bragantina Platform, in the municipality of Capanema and Primavera, continental region of the northeast of the state of Pará. The apparent resistivity data of the electrical soundings were processed using the IPI2win program, which is designed to perform automatic 1D inversions, correlating them whenever possible with the lithological profiles of wells, available in the online platform of the Groundwater Information System (SIAGAS ), with the purpose of adjusting the thickness values of the layers (provided by the lithological profiles) with the the initial geoelectric model solution of and estimating the resistivities of each layer according to the mineralogical composition described in the wells. The results of the electrical soundings carried out in this work were satisfactory, since they allowed to differentiate the possible contact between the Pirabas Formation with the crystalline basement at a depth of around 50 meters in the municipality of Capanema, due to the strong resistivity contrast, and in the Pirabas and Barreiras Formations, around 9 meters deep. Kew-